Comparison of Efficacy between Tamsulosin and Finasteride on Symptomatic Benign Prostatic Hyperplasia - Hassan, M; Parveen, F; Shamsuzzaman, AK; Kibria, MD (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 154-159 The abstract of this article is available on the PubMed website